MyD88 in Macrophages Enhances Liver Fibrosis by Activation of NLRP3 Inflammasome in HSCs - Shuang Ge (MDPI AG, 2021)
Chronic liver disease mediated by the activation of hepatic stellate cells (HSCs) leads to liver fibrosis. The signal adaptor MyD88 of Toll-like receptor (TLR) signaling is involved during the progression of liver fibrosis. However, the specific role of MyD88 in myeloid cells in liver fibrosis has not been thoroughly investigated. In this study, we used a carbon tetrachloride (CCl4)-induced mouse fibrosis model in which MyD88 was selectively depleted in myeloid cells. MyD88 deficiency in myeloid cells attenuated liver fibrosis in mice and decreased inflammatory cell infiltration. Furthermore, deficiency of MyD88 in macrophages inhibits the secretion of CXC motif chemokine 2 (CXCL2), which restrains the activation of HSCs characterized by NLR Family Pyrin Domain Containing 3 (NLRP3) inflammasome activation. Moreover, targeting CXCL2 by CXCR2 inhibitors attenuated the activation of HSCs and reduced liver fibrosis. Thus, MyD88 may represent a potential candidate target for the prevention and treatment of liver fibrosis.